2013
DOI: 10.7314/apjcp.2013.14.11.6357
|View full text |Cite
|
Sign up to set email alerts
|

The MTHFR C677T Polymorphism and Risk of Acute Lymphoblastic Leukemia: an Updated Meta-analysis Based on 37 Case-control Studies

Abstract: Background: The C677T polymorphism of the methylenetetrahydrofolate reductase (MTHFR) has been associated with acute lymphoblastic leukemia (ALL). However, results were conflicting. The aim of this study was to quantitatively summarize the evidence for the MTHFRC677T polymorphism and ALL risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 46 publications
1
14
0
1
Order By: Relevance
“…Hematologic malignancies are a common disease in Asian Pacific areas (Feng et al, 2013;Jiang et al, 2013;Karami et al, 2013;Khodabandehloo et al, 2013;Kooshyar et al, 2013;Li et al, 2013;Liu et al, 2013;Ozbas-Gerceker et al, 2013;Qin et al, 2013;Shan et al, 2013). As our present study confirmed, the level of serum ferritin of patients with hematologic malignancies was significantly increased.…”
Section: Discussionsupporting
confidence: 78%
“…Hematologic malignancies are a common disease in Asian Pacific areas (Feng et al, 2013;Jiang et al, 2013;Karami et al, 2013;Khodabandehloo et al, 2013;Kooshyar et al, 2013;Li et al, 2013;Liu et al, 2013;Ozbas-Gerceker et al, 2013;Qin et al, 2013;Shan et al, 2013). As our present study confirmed, the level of serum ferritin of patients with hematologic malignancies was significantly increased.…”
Section: Discussionsupporting
confidence: 78%
“…Incidence of ALL declines with age nonetheless, its prognosis in adults has always been inferior to children (Faderl et al, 2010;Jinnai et al, 2010). Several age dependent biological and host factors have been described (Jiang et al, 2013;Wang et al, 2014) including, differences in sensitivities of leukemic cells to corticosteroids, metabolism of chemotherapy (Kaspers et al, 1995), depleted marrow reserve and increased extramedullary toxicity (Mishra et al, 2006;Ribera and Oriol, 2009). However, the most important differences lie in cytogenetic and molecular characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…
Asian Pac J Cancer Prev, 15 (15), 6211-6217
IntroductionAcute lymphoblastic leukemia (ALL), the most common malignancy in children (Linabery and Ross, 2008;Jiang et al, 2013), is a heterogeneous disease, with respect to its underlying cellular and molecular biology (Papaemmanuil et al, 2009), acquired genetic abnormalities, and social clinical responses to combination chemotherapy (Pui et al, 2004). The mechanisms involved in the etiology of childhood ALL remain obscure.
…”
mentioning
confidence: 99%